Cartilage abnormalities and osteophytes in the fingers of elite sport climbers: An ultrasonography-based cross-sectional study. Issue 2 (7th February 2020) - Pastor, Torsten; Fröhlich, Stefan; Spörri, Jörg; Schreiber, Tonja; Schweizer, Andreas
ABSTRACT: The impact of extensive loads on the cartilage of the proximal interphalangeal- (PIP) and distal interphalangeal (DIP) joints of the fingers in elite sport climbers are relatively unknown. The purpose of this study was to investigate the changes in the cartilage of the PIP and DIP joints as well as the existence of osteophytes, in fingers of elite sport climbers with a minimum of 15 years of climbing history. Thirty-one elite male sport climbers and 20 male non-climbers volunteered for the current cross-sectional observation. By means of ultrasonography, the thickness of cartilage of the PIP and DIP joints in a sagittal and frontal plane of the digits II to V of both hands, as well as the existence of osteophytes on the dorsal aspect of the phalanges were assessed. The main results were: (1) cartilage thickness revealed to be significantly greater in climbers than non-climbers, ; (2) larger cartilage thickness differences were found at the DIP joints; (3) while climbers showed a substantial occurrence of osteophytes with highest relative frequencies at Dig III, in the group of non-climbers no osteophytes were observed; (4) small to moderate correlations were found between the cartilage and osteophyte thickness of climbers at the PIP and DIP joints and Dig III. In conclusion, an accumulation of repetitive climbing-related stress to the fingers of elite sport climbers over the career may induce degenerative changes at the PIP and DIP joints.